Os equipamentos culturais públicos e o incentivo à cultura: análise da Lei Rouanet e sua efetividade em acervos arquivísticos e museológicos (1996-2018) - Giseli Milani Santiago Balbino (2020)
Brazil's cultural production owes, to a large extent, tax incentive laws. The Rouanet Law provides, through tax waivers, for a direct financing fund through calls for specific projects (FICART), in addition to the cultural and artistic investment fund, for the financing of culture. The analysis of the complex context in which the tax incentive for culture is inserted is of collective interest and access to information, the role of Information Science as Applied Social Science. The aim of this work is to analyze and measure, in number of projects and monetary values encouraged, the applicability of the Rouanet law, as part of a cultural policy aimed at the archival and museum collections, showing its effectiveness in the valorization of these public cultural facilities. The analysis is justified due to the need to research the patronage of the patronage and the direct application of funds, in the preservation, diffusion and access to the Brazilian public archives and archives, as well as demonstrating the imperative revision in the legislation to encourage Brazilian culture . The methodology consisted of exploratory analysis of data from 1996 to 2018, evaluating projects carried out, verifying the attraction of resources destined for archival and museological heritage, by Brazilian region, in the patronage and agreements category, recorded in reports available on the SalicNet website. To search and retrieve information, the following keywords were used for archival collections, as (CODEARQ): public archive, association, home, center, cinematheque, document management board, space, memory, memorial, foundation, institute, documentation, department, museum of image and sound, nucleus, commission. For the museums, the keywords found in the list belonging to the Brazilian Museums, registered at the Brazilian Museum Institute (IBRAM): academy, amphitheater, aquarium, association, biopark, forest, cultural box, corner, house, mansion, castle, will be used center, science ,, circle, collection, ecomuseum, school, station, space, shipyard, experiment library, exhibition, factory, farm, fortress, fort, foundation, gallery, herbarium, church, island, institution, institute, garden, laboratory, memory , memorial, mine, monument, address, world, museo, museum, nucleus, observatory, order, palace, palace, panteon, state park, national park, art gallery, planetarium, reserve, room, site (historical and archaeological), townhouse, union, plant, zoo. The word “collection” will be used for the same purpose, however, for each recovered project, the “basic project data” was checked on the SalicNet website, to see if it is actually an archival or museum collection. The results point out that for both archival and museological collections, the Rouanet Law is not effective, since the percentages destined are very small, both in the category of patronage and in the values coming from the National Culture Fund.